PELAKSANAAN SANKSI ADMINISTRATIF PADA PERATURAN PRESIDEN TENTANG PENGADAAN VAKSIN DAN PELAKSANAAN VAKSINASI DALAM RANGKA PENANGGULANGAN PANDEMI CORONA VIRUS DISEASE - Januardi Utama, Meita Lefi Kurnia , (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
The global pandemic Covid-19 is a threat to humanity in the world, also in Indonesia, which is an archipelagic country, also feels the danger of Covid-19, therefore the state, in this case the government, as the party that runs the wheels of government, carries out various methods such as implementing social distancing. , health protocols, Large-Scale Social Restrictions (PSBB), Enforcement of Restrictions on Community Activities (PPKM), and implementation of Vaccination activities. To carry out vaccination activities, the government in this case has issued various regulations, one of which is Presidential Regulation Number 14 of 2021 concerning Amendments to Presidential Regulation Number 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Mitigating the Corona Virus Disease Pandemic. In this regulation there are administrative sanctions for people who refuse vaccination activities. From the Implementation of Administrative Sanctions implemented in the Gurun Laweh Nan XX Village, namely by making administrative sanctions in the form of delaying or stopping the provision of social security or social assistance, as well as delaying or terminating services government administration. So that the majority of residents of Gurun Laweh Nan XX Village's goal to want to be vaccinated is to get disbursement of Covid-19 assistance, disbursement of permanent assistance PKH (Family Hope Program) and BPNT (Non-Cash Food Assistance).